The Hidden Metaphysics of J. M. E. McTaggart’s Paradox: Influence on The Analytic Philosophy of Time - Šulcas, Adomas (Problemos, 2024)
This paper discusses the various interpretations of McTaggart’s paradox that have been proposed throughout the 20th and the 21st centuries. It is argued that the traditional interpretation of McTaggart’s paradox, one which states that no metaphysical assumptions are required, is unfounded, but is nevertheless vital to the development of the analytic philosophy of time. To support such a position, various works of McTaggart and R. Ingthorsson are cited, aiming to show the intention of the creator of the paradox. It is argued that if McTaggart’s metaphysical premises are accepted, the potential number of interpretations gets narrowed down; however, it is also shown that many of the critiques and discussions arising from the analytic philosophy of time’s discourse can be relatively easily resolved. It is thus concluded that an interpretation of McTaggart’s paradox that includes his metaphysical premises not only makes the paradox itself less ambiguous, but it also shows the importance of metaphysics to the analytic philosophy of time.
Keywords: J. M. E. McTaggartas; paradoksas; metafizika; analitinė laiko filosofija